Cardiac Proteome Profiling in Ischemic and Dilated Cardiomyopathy Mouse Models - Lu, Danbo; Xia, Yan; Chen, Zhangwei; Chen, Ao; Wu, Yuan; Jia, Jianguo; Sun, Aijun; Zou, Yunzeng; Qian, Juying; Ge, Junbo (Frontiers in Physiology, 2019)
Heart failure is a worldwide pandemic with an unacceptable high level of morbidity and mortality. Understanding the different pathophysiological mechanisms will contribute to prevention and individualized therapy of heart failure. We established mouse models for ischemic cardiomyopathy (ICM) and dilated cardiomyopathy (DCM) by inducing myocardial infarction and Coxsackievirus B3 infection respectively. Isobaric tags for relative and absolute quantitation and liquid chromatography coupled with tandem mass spectrometry technology was used to identify the protein expression profiles in control and failing hearts. A total of 1638 proteins were identified and compared in this proteomics analysis. Among them, 286 proteins were differently expressed. Gene ontology, KEGG pathway and ingenuity pathway analysis was performed to systematically assess the potential connections of the differentially expressed proteins to biological functions. Compared with control group, the differentially expressed proteins derived from the hearts of ICM and DCM mice were partially similar and mainly modulated in oxidative phosphorylation, metabolism and protein folding pathways. Moreover, difference still existed, the differentially expressed proteins between DCM and ICM hearts were significantly modulated in oxidative phosphorylation, metabolic and AMPK signaling pathways. Confirmatory western bolt analysis demonstrated that SDHB was down-regulated in both ICM and DCM hearts, while UQCRQ, GLUT4 and adiponectin were up-regulated in ICM hearts. ATP concentration significantly decreased in both DCM and ICM hearts. The protein expression of phospho-AMPKα decreased significantly in DCM hearts, but increased in ICM. In summary, oxidative phosphorylation, cardiac metabolism and protein folding play critical roles in the pathogenesis of heart failure. The diverse changes in protein expression profiles between failing hearts induced by either myocardial infarction or CVB3 infection demonstrated the heterogeneity of heart failure. Understanding the differences in proteome profiles could offer more precise therapeutic options for heart failure.